Smoking trends and awareness among Indian university students: A qualitative study - S. Naganandini; T. Seemadevi; Alexander Maniangat Luke; Mohamed Saleh Hamad Ingafou (Heliyon)
Introduction: Adolescence and early adulthood are recognized as the most vulnerable periods for smoking initiation in India. This is likely due to the increased freedom that young adults have to experiment with different identities and behaviors. Objective: To explore the background of smoking initiation, understand the motivators and barriers to quitting smoking, and assess university students' perceptions and knowledge of Tobacco Cessation Centers (TCCs). Method: Using a combination of snowball and purposive sampling, 20 university students were selected for face-to-face semi-structured interviews. Data collection continued until theoretical saturation was reached, and a thematic framework was applied for data analysis. Results: Qualitative analysis revealed that smoking typically begins in school, driven by peer pressure, socialization, family influence, and stress relief. While many students express a desire to quit for health, financial, and cosmetic reasons, they face challenges due to easy access to cigarettes, peer pressure, nicotine addiction, and the habit of using smoking as a stress reliever. Awareness of Tobacco Cessation Centers among students is limited, with most preferring cost-effective or free services. Conclusion: The results emphasize the significant impact of peer influence on students, indicating a need for group interventions. Incorporating stress reduction techniques into tobacco cessation programs is crucial for those who use smoking as a means of stress relief. Additionally, raising awareness about Tobacco Cessation Centers in college settings is essential. Healthcare professionals developing smoking prevention programs should consider adolescents' perspectives, addressing both health consequences and social factors to enhance the programme effectiveness.